2021
DOI: 10.1111/inm.12912
|View full text |Cite
|
Sign up to set email alerts
|

Digital risks and adolescents: The relationships between digital game addiction, emotional eating, and aggression

Abstract: Nowadays, weight gain and obesity are major health-threatening issues for children. Emotional eating, a negative health condition that can lead to obesity in children, is a defence mechanism for coping with negative emotions. This cross-sectional study aimed to evaluate the relationships between emotional eating behaviour and digital game addiction, which can cause stress and aggression in adolescents. This study was conducted with 856 adolescents from the Mediterranean region of Turkey. The data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 50 publications
1
20
0
2
Order By: Relevance
“…Dijital oyun bağımlılığına ilişkin literatür incelendiğinde çocuklar ve ergenlerle yürütülen çalışmaların çoğunlukta olduğu görülmektedir (7)(8)(9)(10)(11). Bununla birlikte yetişkinlerle yürütülen çalışmalar da bulunmaktadır (2,(12)(13)(14)(15).…”
Section: Introductionunclassified
“…Dijital oyun bağımlılığına ilişkin literatür incelendiğinde çocuklar ve ergenlerle yürütülen çalışmaların çoğunlukta olduğu görülmektedir (7)(8)(9)(10)(11). Bununla birlikte yetişkinlerle yürütülen çalışmalar da bulunmaktadır (2,(12)(13)(14)(15).…”
Section: Introductionunclassified
“…In addition, studies have shown that children or adolescents with gaming addiction are more likely to develop physical health problems such as obesity and insomnia. 6 , 7 They are also more likely to exhibit aggression, 8 impulsive behaviours, and psychiatric symptoms such as obsessive-compulsive disorder. 9 Children and adolescents with gaming addiction are prone to risky online behaviours such as cyberbullying, in which the perpetrator causes malicious, repetitive, and hostile harm to individuals or groups via the internet.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of online learning contrast with a possible long-term risk of prolonged screen use (Wong 2021). Considering that young people also reinforced their social network with their friends and peers in this manner, the risk of misuse of these technologies has risen, which is associated with other health problems (Caner & Evgin 2021). Under such circumstances, children, and adolescents' behaviours, such as physical activity, were drastically impacted due to the prolonged home confinement (Bates et al 2020;Xiang et al 2020).…”
Section: Introductionmentioning
confidence: 99%